Genetic Screens to Identify Elements of the Decapentaplegic Signaling Pathway in Drosophila - Raftery, L. A. (1995)
Pathways for regulation of signaling by transforming growth factor-β family members are poorly understood at present. The best genetically characterized member of this family is encoded by the Drosophila gene decapentaplegic (dpp), which is required for multiple events during fly development. We describe here the results of screens for genes required to maximize dpp signaling during embryonic dorsal-ventral patterning. Screens for genetic interactions in the zygote have identified an allele of tolloid, as well as two novel alleles of screw, a gene recently shown to encode another bone morphogenetic protein-like polypeptide. Both genes are required for patterning the dorsalmost tissues of the embryo. Screens for dpp interactions with maternally expressed genes have identified loss of function mutations in Mothers against dpp and Medea. These mutations are homozygous pupal lethal, engendering gut defects and severely reduced imaginal disks, reminiscent of dpp mutant phenotypes arising during other dpp-dependent developmental events. Genetic interaction phenotypes are consistent with reduction of dpp activity in the early embryo and in the imaginal disks. We propose that the novel screw mutations identified here titrate out some component(s) of the dpp signaling pathway. We propose that Mad and Medea encode rate-limiting components integral to dpp pathways throughout development.